Ultrathin epitaxial InAs layer relaxation on cross-hatch stress fields. Issue 31 (7th July 2016) - Eiwwongcharoen, Win; Nakareseisoon, Nitas; Thainoi, Supachok; Panyakeow, Somsak; Kanjanachuchai, Songphol
Abstract : Highly strained InAs layers epitaxially grown on GaAs/InGaAs cross-hatch surfaces may relax via multiple pathways, resulting in morphologies such as quantum wires, quasi-three-dimensional quantum dots and micron-sized pyramids. Abstract : Thin, highly-strained InAs layers epitaxially grown on GaAs/InGaAs cross-hatch surfaces undergo postgrowth transformations that yield several morphologies ranging from aligned quantum wires to quantum dots and micron-scale pyramids. The shape varieties result from the multiple pathways created from the combined/competitive effects of asymmetric adatom diffusions, subsurface stress fields and misfit energy minimization. These morphologies reveal the multiple outcomes of metastable states between the two- and the three-dimensional transition that if properly captured and engineered may open up new windows of opportunities both in devices such as sensors and in fundamental quantum studies.